Physical and psychological readiness of Aceh’s martial arts athletes for the Indonesia's National Sports Week - Mansur, Mansur; Akbari, Myrza; Ifwandi, Ifwandi; Rubio, Aaron (Tanjungpura Journal of Coaching Research, 2026)
Background Physical and psychological readiness are interrelated components of athletic preparation, particularly in martial arts, where athletes must combine high levels of strength, endurance, speed, flexibility, technical execution, concentration, emotional control, and self-confidence during competition. As Aceh prepares to train martial arts athletes for the 2028 Indonesia's National Sports Week (INSW), monitoring their multidimensional readiness is necessary to identify strengths, detect areas requiring support, and guide evidence-based training programs. Objectives The purpose of this study is to describe the physical and psychological readiness of martial arts athletes participating in the Aceh Provincial Sports Committee’s development program for the 2028 INSW. Methods A cross-sectional survey was completed by 213 athletes from pencak silat, taekwondo, fencing, karate, kempo, tarung derajat, kickboxing, hapkido, wushu, and muaythai. The questionnaire assessed perceived physical readiness (strength, endurance, speed, flexibility, and injury/recovery status) and psychological readiness (motivation, self-confidence, emotional control, concentration, and management of competitive anxiety). Scores were summarized on a 0–100 scale. Descriptive statistics and Pearson's correlation were calculated at α = .05. Results Mean perceived physical readiness was 82.64 ± 8.91 and mean psychological readiness was 78.27 ± 9.35; overall readiness was 80.46 ± 8.23. The highest descriptive scores were observed in pencak silat (physical: 86.3; psychological: 82.4), whereas fencing had the lowest scores (78.9 and 75.3, respectively). Physical and psychological readiness were positively correlated (r = .68, p < .001). Because individual-level test statistics were unavailable for the sport and sex comparisons, between-group differences were interpreted descriptively. Conclusion The athletes reported generally high readiness, but psychological readiness lagged behind physical readiness. Indonesian National Sports Committee (INSC) Aceh should complement conditioning and technical preparation with systematic mental-skills support, recovery and injury surveillance, and repeated multidimensional monitoring. Objective fitness tests and prospective performance outcomes are required before these self-reported scores can be used to predict INSW performance.